Rupture History of the 13th November 2017 Mw 7.3 Iran-Iraq Border Region Earthquake Based on Teleseismic Data - Deyu Yin; Qifang Liu; Yuexin She; Yun Dong (Advances in Civil Engineering)
We have examined the temporal and spatial slip distribution of the 2017 Mw 7.3 Iran-Iraq border region earthquake, utilizing 49 broadband teleseismic P-wave records. Based on the nonnegative least square method and multi-time window, a finite fault model was used to parameterize the rupture process. According to the L-curve, the optimal inversion result was detected. The inversion results showed that the earthquake was a shallow-dip thrusting event. Rupture duration was 20 s, and the total seismic moment was 0.9 × 1020 N·m. There was only one asperity in the fault plane, which indicated the rupture process was simple. The slip was mainly distributed around the initial rupture point, dominated by thrust motion with a small amount of right-lateral strike slip, and the maximum slip was 5.2 m, located on a subfault of the initial rupture. The entire rupture lasted 20 s, and 75% of the energy was released in the first 10 s. The rupture area was 825 km2, and the estimated static stress drop was 6.1 MPa.